Pendampingan Perancangan Tata Letak Produksi Kue dengan Pendekatan Activity Relationship Chart di Kabupaten Gunung Kidul Yogyakarta - Hutauruk, Martinus Robert (Warta LPM, 2024)
Hapsari Cookies is a Small and Medium Enterprise (SMEs) that specialises in producing peanut cookies using home industry methods. The company is progressively transitioning into self-sufficient production. This SMEs employs a significant workforce, and the primary source of peanuts as raw material is the local community surrounding the business premises. Efficient management is crucial for enhancing business empowerment. Hapsari cookies benefits from a strategically positioned business site, complemented by a proficient workforce, advanced machinery, and necessary equipment. However, it has not yet implemented an improved manufacturing operating layout system, which has hindered its ability to optimise its business outcomes. Conversely, the product market has achieved the same magnitude as that of Java and Bali. This condition poses an indirect hindrance to operational procedures and business management. The objective of implementing this community service activity (PKM) is to facilitate the development of a novel and suitable factory layout. The client's cooperation (Hapsari Cookies) has resulted in the establishment of a new factory by using the ARC (Activity Relationship Chart)relationship diagram model, as indicated in this PKM activity. It has the capability to enhance the efficiency and effectiveness of corporate operations, hence maximising business performance.